19. EVALUATION OF NUTRITIONAL STATUS AND MICRONUTRIENT LEVELS IN CHILDREN WITH CHRONIC LIVER DISEASE AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the nutritional status and investigate the levels of certain micronutrients in children with chronic liver disease at Nghe An Obstetrics and Pediatrics Hospital in 2023. Subjects and Methods: A cross-sectional descriptive study was conducted on all children with chronic liver disease who were under monitoring and treatment at Nghe An Obstetrics and Pediatrics Hospital from January 2023 to October 2023.Results: The study involved 37 children with chronic liver disease receiving treatment at Nghe An Obstetrics and Pediatrics Hospital to assess deficiencies in certain micronutrients. Male children accounted for 51.4%, while females accounted for 48.6%. The mean age of the study population was 29.7 ± 36.7 months. Children under 1 year of age constituted the largest proportion at 48.7%, with a male-to-female ratio of approximately 1:1. The most common cause of chronic liver disease was viral hepatitis, representing 48.6%. Micronutrient deficiencies were observed at varying rates: zinc (59.5%), vitamin D (48.6%), and vitamin K (8.8%). Deficiencies in calcium, iron, and magnesium were lower, at 43.2%, 40.5%, and no cases of magnesium deficiency, respectively. Overall, micronutrient deficiencies were most prevalent in children under 5 years of age.Conclusion: Micronutrient deficiencies remain relatively common among children with chronic liver disease. Children under 5 years old have a higher prevalence compared to other age groups. Regular assessments of micronutrient levels in children with chronic liver disease are essential.
Keywords: Chronic liver disease; micronutrient deficiency; children